Control systems - Bolton, W. (William), 1933-
Working through this student-centred text readers will be brought up to speed with the modelling of control systems using Laplace, and given a solid grounding of the pivotal role of control systems across the spectrum of modern engineering. A clear, readable text is supported by numerous worked example and problems. * Key concepts and techniques introduced through applications * Introduces mathematical techniques without assuming prior knowledge * Written for the latest vocational and undergraduate courses.